Hubungan antara cara gaya keibubapaan ibu dan temperamen dengan masalah penyesuaian tingkah laku kanak-kanak prasekolah - Ismail, Nellie; Mohd Adnan, Nur Amani (Universiti Kebangsaan Malaysia, 2021)
Parenting styles and child individual differences such as temperament play a significant role on behavioral adjustment problems among preschool children. Thus, this study aims to determine the relationship between maternal parenting style and temperament with preschool children’s behavioral adjustment problems. A total of 375 mothers of children aged between four to six were selected using simple random sampling techniques. Maternal parenting style was measured using the Parenting Style and Dimensions Questionnaire (PSDQ) and temperament was measured using the Emotionality, Activity, and Sociability Temperament Survey (EAS). Behavioral adjustment problem was measured using the Strength and Difficulties Questionnaire (SDQ). The results revealed that maternal authoritarian parenting style, maternal permissive parenting style and child’s temperament (emotionality) were associated with higher levels of preschool children’s behavioral adjustment problems. These findings have implications for professionals in the field of family and parenting to design an effective preventive intervention in which aspects of the relationship building skills and the establishment of a balanced discipline should be emphasized to parents. In addition, children also need to be equipped with knowledge on emotional control so that they are not easily stressed when faced with various situations that occur in their daily lives either at home or at school.